Social networks and information exchange for climate change adaptation in livestock farming in Senegal - Mbaye, Therese; Houessionon, Prosper; Govoeyi, Benoit; Wane, Abdrahmane; Worou, Nadine; Whitbread, Anthony (International Livestock Research Institute, 2025)
This study analyzes how information networks influence livestock farmers’ adaptation to climate change in Linguere, Senegal. Data from 450 randomly selected households reveal large, predominantly male-headed families with limited education. Social Network Analysis (SNA) shows that AICCRA is the main intermediary for climate information, followed by friends and community radios. These actors play key bridging roles, while NGOs, extension, and feed dealers remain peripheral. The findings highlight the dominance of informal social and community-based information channels over institutional ones. Strengthening links between formal and informal actors could enhance the diffusion of climate adaptation information and improve farmers’ resilience.